PEMANFAATAN ARTIFICAL INTELLIGENCE (AI) DALAM PEMBELAJARAN DAN DILEMA KEJUJURAN AKADEMIK PADA PENGGUNAAN CHATGPT DI SMKN 1 CUGENANG-CIANJUR - Endi Suhendi; Windary Sri Patimah; Elih Herliati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of Artificial Intelligence (AI), particularly ChatGPT, has provided various benefits in the learning process. However, alongside its advantages, the use of AI has also raised concerns regarding academic integrity, especially in examinations and learning assessments. This study aims to examine the utilization of ChatGPT in supporting students’ learning activities and to explore the academic integrity dilemmas arising from its use. The research employed a qualitative approach with a case study method conducted among students of Class XI MPLB 1 at SMKN 1 Cugenang, Cianjur. Data were collected through observation, interviews, and documentation, while data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that ChatGPT is widely used by students to search for information, understand difficult learning materials, summarize content, and generate ideas for completing assignments. The use of AI has been shown to improve the effectiveness and efficiency of the learning process. Nevertheless, the study also found the potential misuse of AI, particularly when it is employed to obtain instant answers during examinations, which may undermine academic integrity. Therefore, teacher supervision, digital literacy enhancement, and the cultivation of ethical values and responsibility are essential in guiding students’ use of AI technology. When utilized wisely and ethically, AI can serve as a valuable learning support tool without compromising students’ academic integrity.